Racial and ethnic discrimination in Portugal in times of pandemic crisis - Casquilho-Martins, I.; Belchior-Rocha, H.; Alves, D. R. (Social Sciences, 2022)
During the last two years, the pandemic has dominated the public attention and debate around the world, centering on socio-economic aspects and having camouflaged other social, cultural and even environmental issues. This study sought to analyze ethno-racial discrimination processes, identifying significant events in Portugal during the period of the current global crisis. We utilized document analysis of national and international reports produced in the last five years, complementing with secondary statistical data and the analysis of online news and users’ comments published in national media during the last two years. The results show that, although there has been a development in Portuguese legislation and in anti-discrimination measures, there has been an increase in racist and xenophobic phenomena in Portugal. Citizens’ perceptions, indicators and reports from official bodies show evidence of discriminatory behavior. Additionally, within this framework, we see a greater political presence of extreme right-wing movements, as well as an increase in hate speech in online news comments. Thus, although there is an awareness of the seriousness of these phenomena, there is an urgent need for actions against racial and ethnic intolerance and greater effective measures for ideological crimes.